2016
DOI: 10.1016/j.neuroimage.2015.09.068
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous transcranial direct current stimulation (tDCS) and whole-head magnetoencephalography (MEG): assessing the impact of tDCS on slow cortical magnetic fields

Abstract: Transcranial direct current stimulation (tDCS) can influence cognitive, affective or motor brain functions. Whereas previous imaging studies demonstrated widespread tDCS effects on brain metabolism, direct impact of tDCS on electric or magnetic source activity in task-related brain areas could not be confirmed due to the difficulty to record such activity simultaneously during tDCS. The aim of this proof-of-principal study was to demonstrate the feasibility of whole-head source localization and reconstruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…Investigators have attempted to quantify the nature of tDCS effects on physiology using EEG (e.g., (Gall et al, 2015; Reinhart & Woodman, 2015; Reinhart, Zhu, Park, & Woodman, 2015)), fMRI (e.g., (Alekseichuk, Diers, Paulus, & Antal, 2015; Amadi, Ilie, Johansen-Berg, & Stagg, 2013; Antal, Polania, Schmidt-Samoa, Dechent, & Paulus, 2011; Hilgenstock, Weiss, Huonker, & Witte, 2016; Hunter et al, 2015; Spiegel et al, 2013)), and MEG (Garcia-Cossio et al, 2015; Hanley, Singh, & McGonigle, 2015; Marshall, Esterer, Herring, Bergmann, & Jensen, 2015; Soekadar et al, 2013). However, there has been little consensus across studies, especially those with similar task parameters.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Investigators have attempted to quantify the nature of tDCS effects on physiology using EEG (e.g., (Gall et al, 2015; Reinhart & Woodman, 2015; Reinhart, Zhu, Park, & Woodman, 2015)), fMRI (e.g., (Alekseichuk, Diers, Paulus, & Antal, 2015; Amadi, Ilie, Johansen-Berg, & Stagg, 2013; Antal, Polania, Schmidt-Samoa, Dechent, & Paulus, 2011; Hilgenstock, Weiss, Huonker, & Witte, 2016; Hunter et al, 2015; Spiegel et al, 2013)), and MEG (Garcia-Cossio et al, 2015; Hanley, Singh, & McGonigle, 2015; Marshall, Esterer, Herring, Bergmann, & Jensen, 2015; Soekadar et al, 2013). However, there has been little consensus across studies, especially those with similar task parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the eloquent study by Hanley and colleagues showed that occipital gamma oscillations were only modulated during tDCS when the stimulation was applied using an electrode configuration distant from the occipital cortex (i.e., involving the motor and frontal cortices, (Hanley et al, 2015)), whereas the study by Marshall et al reported no differences in induced oscillatory during anodal or cathodal occipital stimulation (Marshall et al, 2015). Only two other studies have utilized tDCS and MEG, but the goal of these studies was to evaluate whether online tDCS artifacts precluded accurate MEG source reconstruction (Garcia-Cossio et al, 2015; Soekadar et al, 2013). Both studies found that tDCS artifacts could be effectively removed from the MEG signals to enable accurate localization of responses (Garcia-Cossio et al, 2015; Soekadar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because electrical stimulation affects large areas of the brain cortex, tDCS-induced cortical modification should result in a complex combination of both local and global excitation/inhibition phenomena (Borchers et al, 2012). To try to explain these alterations and to gain new insight into these mechanisms, tDCS and electroencephalographic (EEG) recordings have been used in sequential offline (Miniussi et al, 2012), and online tDCS-EEG approaches (e.g., Accornero et al, 2014;Baxter et al, 2014;Mangia et al, 2014), or in combination with other techniques (Hunter et al, NeuroImage xxx (2016) 2013), such as transcranial magnetic stimulation (TMS) (Pellicciari et al, 2013;Romero et al, 2014), magnetoencephalography (e.g., Garcia-Cossio et al, 2015) and electromyography (EMG) (Dutta et al, 2014). Until now, studies using EEG have shown how the tDCS induces polarity-specific on brain activity oscillations in different frequency bands (Kirov et al, 2009;Miller et al, 2015;Notturno et al, 2014;Song et al, 2014;Spitoni et al, 2013;Ulam et al, 2014).…”
Section: Introductionmentioning
confidence: 99%